2010 A(H1N1) vaccination in pregnant women in Brazil: identifying coverage and associated factors - Raul Andres Mendoza-Sassi; Juraci Almeida Cesar; Jussara Maria Cagol; Ivanise Almeida Duarte; Luana Mostardeiro Friedrich; Viviane Kubiszewski dos Santos; Linjie Zhang (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
We studied vaccination coverage and its associated factors in the 2010 pandemic influenza vaccination of Brazilian pregnant women. A cross-sectional study of pregnant women who had given birth was performed in a municipality in southern Brazil, in 2010. Data about vaccination against A(H1N1) and sociodemographic characteristics, morbidities and prenatal care were collected. Statistical analysis was performed using a Poisson regression. Coverage was 77.4%. Most were vaccinated in the public sector (97.6%) and in the second trimester (47%). Associated factors that increased vaccination were marriage, older age, first income quartile, prenatal care and influenza before pregnancy. Education and skin color were not significantly associated with vaccination. The vaccination campaign was extensive and exhibited no inequality. Prenatal care was the factor that most affected vaccination coverage, reflecting its importance for vaccination campaign success.